Illustrated dictionary of biology - "Stockley, Corinne" (Usborne London, 2011)
Suitable for students studying for their SATs and GCSE's, this title is split into 5 colour coded sections covering various aspects of the curriculum, such as ecology, zoology and human biology, as well as a general information section which includes essential charts and tables.